(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Neuroleptic Malignant Syndrome is rare and potentially life-threatening reaction due to antipsychotic drugs. Over the last decade1000 cases of neuroleptic malignant syndrome have been reported worldwide and the first case was reported in 1950. EPIDEMIOLOGY: Neuroleptic malignant syndrome is a life-threatening complication. First mortality was reported in the year1960 and it accounts to 76 percentage. In recent years due to the awareness on its complications the mortality rate has declined to10-20 percentage. Clinical features: Neuroleptic Malignant Syndrome is a clinical phenomenon exhibiting high fever, unstable mental state, autonomic dysfunction, rigidity of muscles, tachycardia, hypertension or hypotension, diaphoresis, tremor, incontinence, tachypnoea or hypoxia. Case discussion : A 28 years old male who is a known case of bipolar affective disorder with episodes of mania, was started on Inj.Haloperidol 5mg and Tab.Olanzapine 10mg. He presented with tachycardia, muscle rigidity, fever and increased serum creatine kinase levels after 4 days of administration of drugs and was diagnosed as Neuroleptic Malignant Syndrome. Conclusion: Neuroleptic Malignant Syndrome is a life-threatening condition, if not attended to may end up fatal. Awareness about Neuroleptic malignant syndrome due to neuroleptic medication, its early diagnosis, prompt treatment and follow up by physician on neuroleptic drugs has shown prevention of complications and better therapeutic outcomes.